Developing mentoring relationships among collegiate coaches using developmental leadership strategies - McKinney, L. (Leadership Education Capstones, 2020)
A mentor is described as a role model with influence on another`s professional career (Abiddin, 2006). Mentoring comes from a development of an individual (Abiddin). Where this development is the growth of the individual to develop a leadership style (Day, 2011; Day et al., 2014). The purpose of this study is to explore how developmental leadership can help increase mentoring relationships between collegiate coaches in Division II athletics. The experiences of this phenomenon among collegiate coaches gives the opportunity to hear from them the individuals directly involved in these mentoring relationships within the program striving for continuous growth. This study utilizing a qualitative research design with a grounded theory approach to explore the mentoring relationships that develop over time amongst collegiate coaches. Interview rich narrative data will take place to better uncover a theoretical perspective grounded in the data. With these in-depth interviews seven unique themes developed in the study: (a) indirect mentoring relationships, (b) Years of learning to build experience, (c) Positive & Negative dynamics, (d) Intentional observation, (e) Intrapersonal leader, (f) Interpersonal leader, and (g) Group dynamics. Following the one-on-one interviews, documents and observations, the researcher draws the following conclusions from this study: most mentoring relationships are unofficially assigned to individuals, own experience is developed over years of learning from another, leadership style comes with taking the good and bad aspects from what has been learned, years of development has helped individuals find their true self as a leader, and keeping connections with mentors and mentees' builds long-term relationships.